Gender Equality Toward Women in Higher Education - Tuzara, Novia; Khairat, Annisaul (Darul Yasin Al Sys, 2023)
Education is the right of everyone, both men and women, to equal treatment and opportunity. The world of education should be a place to build good sexual relations in social life. Gender equality means that there are no differences in the aspects of the roles and positions of women and men. The purpose of this research is to find out: (1) What is the status of women's equality at UIN Mahmud Yunus Batusangkar 2) What do women think about gender equality. The method used in this research is a qualitative method with a descriptive approach. . Data collection techniques used in this study were observation, interviews and literature study from various sources related to this research. The technique used in the selection of informants is a purposive sampling technique. The results of this study indicate that forms of discrimination against women still exist in tertiary institutions, even though the issue of gender equality is receiving increasing attention. In addition, women often consider themselves weaker than men, which is one of the reasons for gender inequality against women themselves.